EPIDEMIOLOGY OF PITYRIASIS VERSICOLOR IN ELEMENTARY SCHOOL CHILDREN IN THE BANTAR GEBANG, BEKASI - Anindita, Reza; Eka Wahyu Wulandari; Maulin Inggraini; Melania Perwitasari; Maya Uzia Beandrade; Dede Dwi Nathalia; Intan Kurnia Putri (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Pityriasis versicolor (PV) is a disease caused by a superficial fungus, namely Malassezia furfur. This disease is chronic with skin appearance that has characteristics in the form of well-defined skin lesions and white (hypopigmentation) and pink to brownish (hyperpigmentation). PV disease causes itching and a psychological impact in the form of a decrease in self-confidence. The purpose of this study was to determine the percentage of PV incidence in elementary school children at the Garbage Disposal Site, Bantar gebang, Bekasi, West Java. This type of research is quantitative and descriptive with a cross-sectional design. The research sample consisted of 87 elementary school students in grades 1 and 2 who were selected based on inclusion criteria, namely the presence of hypopigmented and hyperpigmented lesions. The examination was carried out microscopically with the solatip method using 10% KOH. Data analysis was performed by using descriptive statistical tests. The results of this study showed that there were 35 (40%) students who were positively infected with PV, which was confirmed by the presence of spores and hyphae of the fungus M. furfur. The age most affected by PV is 7 years old, with a percentage of 17 (49%) students, while the percentage of the sex most affected by PV is male, with as many as 23 (53%) students. The study concludes that the prevalence of children in grades 1 and 2 at Yayasan Dinamika Indonesia Elementary School around the Bantargebang landfill, Bekasi, West Java, is in the middle category. The factors that influence the incidence of PV in this study are outdoor activities, which cause the facial area to sweat easily, and lack of personal hygiene.